MICROBICIDAL AND CYTOTOXIC ACTIONS OF METHANOLIC CRUDE EXTRACTS OF A. MULTIFLORA.-ROXB - Mobarak, S. A.; Hossain, Shafayat; Mia, Sagir (International Journal of Current Pharmaceutical Research, 2015)
Objective: The study presented here was carried out for the evaluation of microbicidal and cytotoxic potential of methanolic extract of leaves of Ammannia multiflora. The microbicidal activity was tested against 16 bacteria. The cytotoxic activity was tested against brine shrimp species Artemia salina. Methods: The microbicidal effect of the plant extracts was tested in vitro by the disc diffusion method with 16 standard bacterial strains. Artemia salina; a brine shrimp species; was used to assess cytotoxic activity. Results: Among the subjected 16 different bacteria; in case of S. boydii; the zone of inhibition was higher (22.0 mm) at 500 µg/ml concentration. Whereas in the case of E. foecalis, the zone of inhibition was higher (8.0 mm) at 250 µg/ml concentration. In S. pyogenes; zone of inhibition was higher at 500 µg/ml concentration (13.0 mm). The growth of S. saprophyticus (9 mm), S. agalactiae (7 mm) and S. sonnei (7 mm) was also moderately inhibited. The extract exhibited effectiveness against 7 different species of bacteria out of 16. Cytotoxic effect was determined in lethality bioassay of brine shrimp species Artemia salina. The plant extracts exhibited significant cytotoxic property which was reflected in LC50 and LC90values of 20.42µg/ml and 229.09 µg/ml respectively. Cytotoxic property was found as dose dependent manner. Conclusion: These results suggest that, Ammania multiflora can effectively be used for its significant microbicidal action. It is also effective as cytotoxic agent and thus, could justify its use in traditional medicine.